ÍNDICES BIOMÉTRICOS DE JUVENIS DE PACU CULTIVADOS EM TANQUES-REDE E SUBMETIDOS À RESTRIÇÃO ALIMENTAR - de Sá Cavalheiro , Matheus; Hugo Benassi Mendez , Victor; Soares Oliveira, Nandara; Mara Gomes Acunha , Rubia; Martins Wanderley, Alysson; Meldau Campos, Cristiane (ANAIS DO ENIC, 2026)
-